COVID-19 pneumonia: ARDS or not? - Gattinoni, Luciano; Chiumello, Davide; Rossi, Sandra (Critical care (London, England), 2020)
The lung’s gas volume is high, the recruitability is minimal, and the hypoxemia is likely due to the loss of hypoxic pulmonary vasoconstriction and impaired regulation of pulmonary blood flow. [...]severe hypoxemia is primarily due to ventilation/perfusion (VA/Q) mismatch. [...]some of these hypoxemic patients receive CPAP or non-invasive ventilation before ICU admission and present with very high respiratory drives, vigorous inspiratory efforts, and highly negative intrathoracic pressures. [...]in addition to viral pneumonia, those patients likely have self-inflicted ventilator-induced lung injury [4]. Acute Respiratory Distress Syndrome N, Brower RG, Matthay MA, Morris A, Schoenfeld D, Thompson BT, Wheeler A. Ventilation with lower tidal volumes as compared with traditional tidal volumes for acute lung injury and the acute respiratory distress syndrome.